Patient-reported outcomes from the phase III IMpassion130 trial of atezolizumab plus nab-paclitaxel in metastatic triple-negative breast cancer - Adams, Sylvia; Dieras, V.; Barrios, C. H.; Winer, E. P.; Schneeweiss, Andreas; Iwata, H.; Loi, S.; Patel, S.; Henschel, V.; Chui, S. Y.; Rugo, H. S.; Emens, L. A.; et al. (Annals of oncology, 2020)
Background: Metastatic triple-negative breast cancer (mTNBC) is incurable. A key treatment goal is providing palliation while maintaining patients' health-related quality of life (HRQoL). IMpassion130 demonstrated progression-free survival benefit with atezolizumab + nab-paclitaxel (A + nP) versus placebo + nab-paclitaxel (Pl + nP) in first-line treatment of mTNBC patients with programmed death-ligand 1 positive (PD-L1+) tumors. We report data on patient-reported outcomes (PROs), which capture patient perspectives of treatment. Patients and methods: Patients with untreated advanced or mTNBC received atezolizumab (840 mg) or placebo every 2 weeks in combination with nab-paclitaxel (100 mg/m(2)) on days 1, 8, and 15 of each 28-day cycle until progression or intolerance. Patients completed the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire (QLQ-C30) and its Breast Cancer Module (QLQ-BR23) on day 1 of each cycle, at end of treatment, and every 4 weeks during 1 year of follow-up. Time-to-deterioration (TTD) in HRQoL (first >= 10-point decrease from baseline lasting two cycles) was a secondary end point. Exploratory end points included TTD in functioning and mean and mean change from baseline scores in HRQoL, functioning, and disease- and treatment-related symptoms. Results: Baseline completion of PROs was 92% (QLQ-C30) and 89% (QLQ-BR23) and remained >80% through cycle 20 in intent-to-treat (ITT) and PD-L1+ patients. No differences between arms in median TTD in PD-L1+ patients were observed for HRQoL {hazard ratio (HR) 0.94 [95% confidence interval (CI) 0.69-1.28]} or physical [HR 1.02 (95% CI 0.76-1.37)] or role [HR 0.77 (95% CI 0.57-1.04)] functioning. Mean baseline scores for A + nP versus Pl + nP for HRQoL (67.5 versus 65.0) and physical (82.8 versus 79.4) and role (73.7 versus 71.7) functioning were comparable between arms and throughout the course of treatment, with no clinically meaningful (>= 10 point) changes from baseline until patients discontinued treatment. No differences in clinically meaningful worsening in treatment symptoms (fatigue, diarrhea, or nausea/vomiting) were observed between arms. Results in ITT patients were similar. Conclusions: A + nP as first-line treatment for mTNBC delayed progression without compromising patients' day-to-day functioning or HRQoL or worsening treatment symptoms.